The relationship between sarcopenia and mental health status in Chinese older adults: the mediating role of activities of daily living - Huaiju Ge; Shilan Yang; Wenyu Su; Weimin Guan; Shihong Dong; Wenjing Chang; Huiyu Jia; Shan Jiang; Di Qin; Guifeng Ma (BMC Geriatrics)
Abstract Background Most existing studies focus on either the relationship between sarcopenia and depressive symptoms or sarcopenia and cognitive functions. Few studies have examined depressive symptoms and cognitive functions simultaneously. This study aimed to analyze the relationship between sarcopenia and both depressive symptoms and cognitive functions in the elderly by introducing activities of daily living to explore the mediating role of activities of daily living between sarcopenia and mental health. Methods This study used data from the 2015 and 2018 China Health and Retirement Longitudinal Study, including a total of 3,552 older adults aged 60 and above. We conducted descriptive statistical analysis and correlation analysis on the data and used seemingly unrelated regression to examine the relationship between sarcopenia, depressive symptoms, and cognitive functions in older adults. Bootstrap mediation analysis was used to further explore the mediating role of activities of daily living in the relationship between sarcopenia and depressive symptoms and cognitive functions in the elderly. Results After adjusting for confounding factors, sarcopenia was positively correlated with depressive symptoms (β = 0.663, p < 0.001) and negatively correlated with cognitive functions (β=-0.748, p < 0.001), indicating a negative impact of sarcopenia on mental health. Activities of daily living mediated the relationship between sarcopenia and mental health, with a stronger mediating effect between sarcopenia and depressive symptoms (18.77%, β = 0.125, 95%CI (0.035, 0.222)) than between sarcopenia and cognitive functions (12.82%, β=-0.099, 95%CI (-0.162, -0.035)). Conclusions Activities of daily living partially mediated the relationship between sarcopenia and mental health status in Chinese older adults. Interventions targeting sarcopenia and activities of daily living may be an effective way to prevent and improve the mental health status of older adults.